Country Insurance : The Role of Domestic Policies - Mauro, Paolo; Becker, Torbjorn; Ostry, Jonathan; Ranciere, Romain (Washington, D.C. : International Monetary Fund, 2007)
This paper focuses on what countries can do on their own-that is, on the role of domestic policies-with respect to country insurance. Member countries are routinely faced with a range of shocks that can contribute to higher volatility in aggregate output and, in extreme cases, to economic crises. The presence of such risks underlies a potential demand for mechanisms to soften the blow from adverse economic shocks. For all countries, the first line of defense against adverse shocks is the pursuit of sound policies. In light of the large costs experienced by emerging markets and developing countries as a result of past debt crises, fiscal policies should seek to improve sustainability, taking into account that sustainable debt levels seem to be lower in emerging and developing countries than in advanced countries. Although much can be accomplished by individual countries through sound policies, risk management, and self-insurance through reserves, collective insurance arrangements are likely to continue playing a key role in cushioning countries from the impact of shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet